Navigating academic transitions: Support and challenges of African international students in community colleges - Ihuoma, Chinwe; Bista, Krishna (Journal of Interdisciplinary Studies in Education, 2025)
This study explores the academic transition experiences of African international students at a U.S. community college, with a focus on institutional support and associated challenges. Using a qualitative single case study approach, in-depth interviews with eight students revealed three central themes: supportive academic environments, academic and cultural challenges, and adaptation to U.S. higher education. While faculty support and peer networks facilitated smoother transitions, communication barriers, unfamiliar instructional methods, and financial difficulties hindered progress. The findings highlight the need for targeted institutional interventions, including multicultural resource centers, improved communication strategies, and expanded on-campus employment opportunities. Guided by Schlossberg’s Theory of Transition, this study offers insights for educators and administrators aiming to foster a more inclusive and supportive campus climate for African international students in community colleges.